PROFIL MAHASISWA SEBAGAI KONSUMEN: PERSPEKTIF MAHASISWA MEMAHAMI MATERI DAN TUGAS KULIAH - Shofiyah, Euis Laelatus; Sisilia, Kristina (2021)
Currently, students at Telkom University are competing to make startups in the technology field. Homelab is a startup in Telkom University that will start releasing online services and a question-and-answer application about students’ college assignments. Currently, Homelab is targeting students in business majors to be their initial target customers. This research will identify university students who need and want to get answers to their coursework—identifying this customer profile by defining customer jobs, pains, and gains. The method used in this research is a qualitative descriptive approach, and the data collection method uses a semi-structural interview technique of university students using purposive sampling. The result of this research is the consumer profile of Homelab, namely students who find it challenging to complete college assignments, students who frequently search for answers on the internet, and those who are willing to pay for a paid online site. The things they avoid are getting unsatisfactory grades or even repeating courses and complex access to online sites. What they want is that they need a website that can help complete coursework, online sites that have references to answer to coursework, an online website that provides complete answers at an affordable price. Student behavior in completing lectures can be used as a guide for the development of related applications that are more accurate and comprehensive.